Estimation of Blood Biochemical Constituents and Cortisol as Stress Predictors and Prognostic Biomarkers in Buffaloes Affected With Uterine Torsion - Selvaraju, Mani; Karthick, Chinnappa; Prakash, Subramaniyan; Periyannan , Mani; Ruthrakumar, Ravichandran (The Indian Journal of Animal Reproduction, 2022)
Full term pregnant buffaloes (n=24) affected with uterine torsion were equally divided into four experimental groups based on duration of uterine duration viz 6-12 hours (Group I); 12-24 hours (Group II); 24-48 hours (Group III) and more than 48 hours (Group IV). The control (Group V) consisted of six normal full term pregnant buffaloes. The experimental buffaloes were treated by modified Schaffer’s method. Those buffaloes, in which detorsion failed following modified Schaffer’s method, were treated by caesarean section. As the duration of uterine torsion increased, there was a corresponding increase in blood glucose levels from Group I to Group IV. There was a definite reduction in serum total protein and albumin concentrations in buffaloes affected with uterine torsion. As the duration of uterine torsion increased, a concomitant increase in blood urea nitrogen (BUN) and greater increase in serum creatinine levels were noticed. The mean creatine phosphokinase (CPK) and aspartate aminotransferase (AST) levels ranged from 152.71±39.09 to 445.30±44.57 and from 80.84±2.19 to 110.83±2.67 U/L, respectively. The successful detorsion in treatment groups caused drastic reduction in serum CPK and AST values at 24 hours after detorsion and 30 days after fetal delivery. The mean serum cortisol level ranged from 44.02±3.30 to 79.39±1.78 ng/ml in buffaloes affected with uterine torsion and it was 12.17±0.54 ng/ml at 24 hours before calving in normally calved buffaloes. Prior to detorsion in all the treatment groups, tremendous increase in mean serum cortisol levels was observed. It can be concluded that serum biochemical parameters and cortisol concentration may help to predict the prognosis of uterine torsion in buffaloes.